Impact of renewable energy in Indian electric power system - V. Saravanan; K. M. Venkatachalam; M. Arumugam; M. A. K. Borelessa; K. T. M. U. Hemapala (Institute of Advanced Engineering and Science, 2021)
This paper addresses the impact of renewable power generation such as photovoltaic and wind energy in the existing power system operations. Various modeling approaches and power quality/reliability analysis of these renewable energy sources in the electric power system by researchers and research organisations and utilities are outlined and their impacts are assessed. Challenges and protection schemes of renewable power integration into the existing grid are discussed through a detailed literature review and study of renewable integration into the Indian power system are outlined including potential planning and policy actions to support renewable energy integration in India.